2018
DOI: 10.3389/fnhum.2018.00341
|View full text |Cite
|
Sign up to set email alerts
|

EEG Resting State Functional Connectivity in Adult Dyslexics Using Phase Lag Index and Graph Analysis

Abstract: Developmental dyslexia may involve deficits in functional connectivity across widespread brain networks that enable fluent reading. We investigated the large-scale organization of electroencephalography (EEG) functional networks at rest in 28 dyslexics and 36 typically reading adults. For each frequency band (delta, theta alpha and beta), we assessed functional connectivity strength with the phase lag index (PLI). Network topology was examined using minimum spanning tree (MST) graphs derived from the functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 92 publications
2
38
2
Order By: Relevance
“…The considered parameter configurations resulted in a low activity state of disconnected nodes (G = 0) and generation of limit-cycle oscillations with an alpha-band frequency when the individual regions were coupled (G > 0). The modelled alpha oscillations have been shown to be dominant in EEG of human resting-state brain activity (Fraga González et al, 2018;Spitoni, Di Russo, Cimmino, Bozzacchi, & Pizzamiglio, 2013) and to interact with BOLD responses (Mayhew, Ostwald, Porcaro, & Bagshaw, 2013).…”
Section: Neural Mass Modelmentioning
confidence: 99%
“…The considered parameter configurations resulted in a low activity state of disconnected nodes (G = 0) and generation of limit-cycle oscillations with an alpha-band frequency when the individual regions were coupled (G > 0). The modelled alpha oscillations have been shown to be dominant in EEG of human resting-state brain activity (Fraga González et al, 2018;Spitoni, Di Russo, Cimmino, Bozzacchi, & Pizzamiglio, 2013) and to interact with BOLD responses (Mayhew, Ostwald, Porcaro, & Bagshaw, 2013).…”
Section: Neural Mass Modelmentioning
confidence: 99%
“…Moreover the reduced connectivity between visual association areas and prefrontal attention areas during tasks may indicate worse integration and modulation of attentional control to visual information in impaired readers ( Finn et al, 2014 ). To summarize, functional connectivity literature suggests broader connectivity deviances in dyslexia that extend beyond the language networks (e.g., Wolf et al, 2010 ; Finn et al, 2014 ; Fraga González et al, 2016 , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the Fourier domain, spectral characteristics of the standard EEG frequency sub-bands, namely delta (δ) (0.5-4 Hz), theta (θ) (4-8 Hz), alpha (α) (8)(9)(10)(11)(12)(13) and beta (β) (13-30 Hz) have been extensively used as input features for the different interictal spike detection and classification algorithms such as Support Vector Machine (SVM) and Artificial Neural Network (ANN) [14]- [20]. We note that in this study as well as others [21], the gamma sub-band (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) was excluded due to the presence of evidence suggesting that the gamma frequency range in scalp EEG recordings may be strongly affected by muscle artifact [22]. In addition, [23] reported that the gamma sub-band yields low reliability graph metrics.…”
Section: Introductionmentioning
confidence: 84%